Access to cultural ecosystem services and how urban green spaces marginalize underprivileged groups - Irvanu Rahman; Armin Grunwald; Somidh Saha (npj Urban Sustainability)
Abstract Rapid urbanization in cities has diminished urban green spaces (UGS), limiting access to recreational opportunities, and affecting social cohesion and mental well-being. We assess the influence of spatially-referenced socioeconomic factors of land value on green space access in Jakarta, Indonesia, to understand environmental justice issues in cultural ecosystem services (CES). Isochrones, gravity model principles, and a participatory spatial mapping survey (n = 638) were used to identify culturally significant UGS and assess their accessibility based on respondents’ residential land value information. Our analysis reveals a stark disparity in access to high-quality CES, with only visitors from high-land-value areas reaching these services within a 60-min pedestrian travel time. Consistent inequality patterns in lower socioeconomic groups reflect structural barriers that limit their access to the cultural benefits of UGS. Our discussion highlights contributions to the field and suggests critical planning directions to improve the quality, quantity, and accessibility of CES.